Bridging Gaps in Integrated Transportation Systems for Sustainable Logistics - Munawar, Soviyan (Yayasan Sinergi Kawula Muda, 2023)
This study offers a narrative literature review on transportation mode integration in logistics distribution, focusing on the interplay between infrastructure development, digital technologies, and collaborative logistics platforms in enhancing multimodal systems. Drawing from databases like Scopus, Web of Science, and Google Scholar, the review highlights how infrastructure serves as the foundation for logistics flow, digital tools facilitate real-time coordination and route optimization, and collaborative platforms support stakeholder alignment, especially in urban settings. Despite advancements, regional disparities in infrastructure, digital capacity, and policy enforcement hinder logistics efficiency. Empirical evidence shows that AI-supported multimodal logistics can reduce delivery times by up to 25% and transportation costs by 18% in dense urban areas. While developed countries leverage innovation and strong frameworks, developing regions struggle with technological access and policy inconsistencies. Sustainability is a recurring theme, with digital tools contributing to emissions tracking and carbon reduction. The study calls for integrated policies, infrastructure investment, and scalable digital solutions, particularly for underserved regions. Key recommendations include strengthening collaborative networks, enhancing digital skills, and implementing region-specific strategies. This review contributes to the global dialogue on sustainable logistics and outlines future research directions to address persistent gaps in multimodal logistics integration.